The Experiences of New-Starters: Remote Working in The Post-COVID-19 Era - Alay, Hazal Koray; DEVECİYAN, MERİ TAKSİ (Sosyoekonomi Derneği, 2023)
This study aimed to understand the experiences of information technology sector employees who started their first job using remote working. A semi-structured interview, one of the qualitative research designs, was used. Twenty-four interviews were conducted to understand the effects of the advantages and disadvantages perceived by the employees regarding the remote working method on their life and career aspects. Two prominent and five sub-themes emerged in this research. The main themes regarding the perceptions of those who start their business life within the scope of remote work and the advantages/disadvantages of working remotely are the sub-themes: perceptions of their managers, career life, corporate culture, work-life balance, and learning processes.
Keywords: Remote Work; New Starters; Learning; Organizational Culture; Work-Life Balance; Job Autonomy; Self-Discipline